2004
DOI: 10.1007/s00251-004-0645-6
|View full text |Cite
|
Sign up to set email alerts
|

A single major chromosomal region controls natural killer cell-like activity in rainbow trout

Abstract: We report the identification of a single major chromosomal region controlling natural killer (NK) cell-like activity in rainbow trout (Oncorhynchus mykiss). A genetic map based on 484 AFLP and 39 microsatellite genotypes from 106 doubled haploid fish was constructed. These fish were produced by androgenesis from a hybrid of two clonal lines divergent in NK-like activity. NK-like activities for 75 of the doubled haploids were quantified by an in vitro chromium release assay utilizing (51)Cr-labeled YAC-1 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Another bony fish, Oreochromis niloticus, possesses a KLR region, containing 26 genes, though more compact than its human counterpart [105]. Other teleosts have NKC genes, including Paralabidochromis chilotes [106] and rainbow trout [107], demonstrating that some of these genes arose in an ancestor common to both humans and bony fish earlier in the gnathostome lineage.…”
Section: Nk Receptor Gene Complexes In Other Speciesmentioning
confidence: 99%
“…Another bony fish, Oreochromis niloticus, possesses a KLR region, containing 26 genes, though more compact than its human counterpart [105]. Other teleosts have NKC genes, including Paralabidochromis chilotes [106] and rainbow trout [107], demonstrating that some of these genes arose in an ancestor common to both humans and bony fish earlier in the gnathostome lineage.…”
Section: Nk Receptor Gene Complexes In Other Speciesmentioning
confidence: 99%
“…The identification of QTL (Quantitative Trait Loci) paves the way for a precise investigation of the molecular genetic basis of traits. While many QTL studies have already been implemented for a range of traits, including growth [22], disease resistance [23-26], temperature tolerance [27], cortisol responsiveness [28] and early maturation [29], very little has been done regarding osmoregulation capacities in rainbow trout. Nichols et al .…”
Section: Introductionmentioning
confidence: 99%
“…Such carefully controlled environmental and genetic conditions strongly suggest that the trade-off between growth rate and sprint swimming ability has a genetic basis; however, it is important to keep in mind that only a limited amount of the available genetic variation within a source stock is contained within a clone. A number of other traits, such as development rate (Robison et al 2001), immune response (Zimmerman et al 2004), disease resistance (Nichols et al 2003), and stress response (Drew et al 2007) have already been shown to have a genetic basis in clonal line crosses.…”
Section: Discussionmentioning
confidence: 98%